AS CORRELAÇÕES ENTRE OS NÍVEIS DE CONSCIÊNCIA DA LIDERANÇA E AS COMPETÊNCIAS GERENCIAIS - Rocha, Carla de Azeredo Coutinho (2008)
This study has the purpose to investigate, between professionals who are studying their MBA's, the correlations of the awareness of leadership and managerial skills. The theory of levels of awareness of the leadership of Richard Barrett (2000) was adopted as the main reference for this theoretical work. It supported the studies of the hierarchy of needs of Abraham Maslow (1999), extending it to higher levels, and the theory of managerial skills of Robert E. Quinn (2003). The methodology used was based on bibliographic review and field research. The bibliographic review refers about the types of leadership and management models and concepts of skills, emphasizing the role of its integration as a factor driving force in the management of people. The field research was based on a data collecting through the application of a structured questionnaire, as the main tool. The results showed different weights and greater expressiveness for some of the correlations between the styles of leadership and managerial skills. The conclusion pointed to imbalances between the styles of leadership and managerial skills.